The Influence of Socio-Cultural and Behavioral Factors on the Risk of NAFLD (Non-Alcoholic Fatty Liver Disease) and MAFLD (Metabolic Associated Fatty Liver Disease): Literature Review - Nainggolan, Fikriyah Arfina; Chairani, Shinta Andria; Nasution, Murni Noviani (JURNAL KESMAS DAN GIZI (JKG), 2025)
Non-Alcoholic Fatty Liver Disease (NAFLD) is the accumulation of liver fat in individuals who are not heavy alcohol users. The term Metabolic Associated Fatty Liver Disease (MAFLD) was introduced to emphasize its association with metabolic syndrome. In addition to classic factors such as obesity, diabetes, and dyslipidemia, socio-cultural factors such as diet, lifestyle, community habits, urbanization, and work culture play an important role in the epidemiology of this disease. This article aims to explore the relationship between socio-cultural factors and the incidence of NAFLD/MAFLD through a review of the latest literature. The literature review was conducted using a narrative approach based on databases. The literature shows that socio-cultural factors influence the risk of NAFLD/MAFLD through various mechanisms, including a shift in diet from traditional patterns to high-calorie and ultra-processed diets, an increase in sedentary lifestyles due to urbanization, and certain cultural perceptions that view obesity as a symbol of prosperity. In addition, social and gender norms also influence physical activity, while family and community support plays an important role in the success of interventions. Socio-cultural factors contribute significantly to the development of NAFLD/MAFLD. Therefore, strategies for the prevention and control of this disease need to integrate the promotion of healthy lifestyles with culturally-based interventions that are sensitive to the local context.